3D organ-on-a-chip: The convergence of microphysiological systems and organoids - Baptista, Leandra S.; Porrini, Constance; Kronemberger, Gabriela S.; Kelly, Daniel J.; Perrault, Cecile M. (Frontiers in Cell and Developmental Biology, 2022)
Medicine today faces the combined challenge of an increasing number of untreatable diseases and fewer drugs reaching the clinic. While pharmaceutical companies have increased the number of drugs in early development and entering phase I of clinical trials, fewer actually successfully pass phase III and launch into the market. In fact, only 1 out of every 9 drugs entering phase I will launch. In vitro preclinical tests are used to predict earlier and better the potential of new drugs and thus avoid expensive clinical trial phases. The most recent developments favor 3D cell culture and human stem cell biology. These 3D humanized models known as organoids better mimic the 3D tissue architecture and physiological cell behavior of healthy and disease models, but face critical issues in production such as small-scale batches, greater costs (when compared to monolayer cultures) and reproducibility. To become the gold standard and most relevant biological model for drug discovery and development, organoid technology needs to integrate biological culture processes with advanced microtechnologies, such as microphysiological systems based on microfluidics technology. Microphysiological systems, known as organ-on-a-chip, mimic physiological conditions better than conventional cell culture models since they can emulate perfusion, mechanical and other parameters crucial for tissue and organ physiology. In addition, they reduce labor cost and human error by supporting automated operation and reduce reagent use in miniaturized culture systems. There is thus a clear advantage in combining organoid culture with microsystems for drug development. The main objective of this review is to address the recent advances in organoids and microphysiological systems highlighting crucial technologies for reaching a synergistic strategy, including bioprinting.